Antegrade intramedullary fixation for adolescent fifth metacarpal neck fracture and its impact on epiphyseal growth - Xiao-Lei Fan (BMC Musculoskeletal Disorders, 2021)
Abstract Background Antegrade intramedullary nailing (AIMN) with Kirschner wire (K-wire) is a minimally invasive osteosynthesis technique. This procedure has been widely performed to treat the fifth metacarpal neck fracture (FMNF) in adults. This study was performed to determine whether using AIMN with a single K-wire to treat FMNF in adolescents would have good clinical and radiographic outcomes. Methods In this retrospective study, 21 children (aged 11–16 years) with FMNF were treated using AIMN with a single K-wire from May 2017 to January 2020 in our hospital. Indications for intervention were severe displacement with malrotation deformity, apex dorsal angulation of greater than 40°, or both. Collected data included apex dorsal angulation, range of motion (ROM) in the fifth metacarpophalangeal (MCP) joint, Visual Analog Scale (VAS) for pain, grip strength, and Disabilities of the Arm, Shoulder, and Hand (DASH) score. Results All patients were followed up for 12–24 months (average, 16.57 months), and all patients obtained anatomical reduction postoperatively. The healing time was 2.69 ± 0.83 months (range, 2–4 months). Average apex dorsal angulation was reduced significantly from 44.49°±2.64° to 15.74°±2.47° (P < 0.001). The average ROM in the MCP joint and apex dorsal angulation of the injured side were not significantly different from those of the uninjured side. The average DASH score was 1.76 ± 1.48 (range, 0–4), the mean VAS was 0.19 ± 0.60 (range, 0–2), and the mean grip strength was 91.55 %±4.52 % (range, 85–101 %). No secondary displacement, dysfunction, nonunion, infection, or osteonecrosis was observed during the follow-up. Although premature epiphyseal closure was found in one patient, no long-term clinical finding of angulation or shortening was identified. Conclusions Antegrade intramedullary fixation with single K-wire was an effective and reliable technique that successfully resulted in good functional and cosmetic outcomes for treating adolescents with FMNF. The impact on the growth plate was low in this population given that most patients were at or approaching skeletal maturity. Level of evidence Level IV.